Forgery of Shari’a rulings in the credit case and it’s efficacy in Figh - et. al., Alireza Rostami, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Following the definitions of verdict, it seems that there is no difference in how shari’a ruling is forged as a real theorem. The fundamentalists have analyzed the falsification of Shari'a rulings in real theorems, without considering the lordship of the Shari'a; while the Lordship of the Shari'a encircling all the worlds and the causes and causes of the unseen and intuition, which is with present knowledge and without transgression and error, it is appropriate that the falsification of the rulings be Personal theorem. what has led to the idea that the method of falsifying the rulings is a real theorem is the manner in which the Qur'an and the Sunnah are addressed; while with a little care and reflection we realize that the speeches are the bearers of the Shari'a rulings, not itself. In addition, the requirement of surrounding the Shari'a is that his credibility be effective in the world of evolution and cause change in the world of evolution if none of the rational credentials has such an effect; That is, the sanctity and legitimacy that the Shari'ah validates, in the world of evolution, it causes the effect and origin of change, while rational prohibitions and discharges do not have such effects.